Clinical guide to antineoplastic therapy a chemotherapy handbook - Gullatte, Mary Magee; Spinks, Renee; Walker, Deborah Kirk; Schwartz, Rowena (Pittsburgh, PA Oncology Nursing Society, 2019)
The world of cancer treatment is changing almost daily. In 2018 alone, the U.S. Food and Drug Administration approved 19 new cancer drug treatments, and many more promising drugs are on the horizon. New therapies include targeted therapies, immunotherapy, drugs associated with cancer genetics, and nanotechnology. A developing treatment is CAR (chimeric antigen receptor) T-cell therapy, which includes the administration of new immunotherapy drugs used for adult patients with certain types of lymphoma and for children and young adults with acute lymphoblastic leukemia. Virtually every single chemotherapy drug comes with its own long list of symptoms, which are only confounded when more than one agent is used in a cancer regimen. Oncology nurses are almost always the providers who intervene when patients experience one or many symptoms; thus, these professionals must remain knowledgeable about the effects of all antineoplastic agents in use. Many of the newer medications have associated symptoms such as skin alterations and intense flu-like symptoms that, until recently, were not the usual mainstay. This handbook was written by a collection of expert oncology professionals to address every facet of antineoplastic therapy, from understanding biomarkers that influence treatment decisions, navigating cost and reimbursement issues, to supporting patients and their families throughout their treatment trajectory and survivorship. A team of nurses, pharmacists, advanced practice providers, social workers, and physicians have contributed to this text and reflects the collaborative nature of the delivery of care to patients. Chapters examine antineoplastic agent use and monitoring, from conventional cytotoxic chemotherapy to clinical trials and survivorship, and include detailed drug monographs for quick access to information. New perspectives and topics, such as biosimilars, help providers appreciate the nuances of the expanding categories of antineoplastic agent use. The approach of including scientific, operational, and psychosocial information across topics ensures the reader gains global information to ideally expand knowledge, increase curiosity, and aid in delivering exceptional care. Similarly, holistic topics, including support services, patient navigation, access devices, and legal concerns provide, a well-rounded approach to subject matter relevant to all disciplines involved in care. This edition of A Chemotherapy Handbook is a key resource for everyone from newly minted practitioners to seasoned veterans involved in oncology patient management"--
Cellular mechanisms of chemotherapy -- Pharmacologic principles of chemotherapy -- Pharmacogenomics and chemotherapy -- Principles and standards of antineoplastic therapy administration -- Administration of hazardous drugs in the perioperative setting -- Immunotherapy : agents and targets -- Targeted therapy : small molecule inhibitors -- Antineoplastic agents -- Antineoplastic regimens -- Stem cell transplantation science and practice -- Clinical trials -- Strategies to improve adherence to oral cancer therapies -- Symptom management -- Intimacy and sexuality concerns of patients receiving chemotherapy -- Late effects of chemotherapy -- Cancer survivorship support -- Maximizing outpatient reimbursement for antineoplastic agents -- Legal issues in cancer care -- Complementary and alternative medicine therapies in oncology practice -- Botanicals in cancer care -- Access devices -- Biosimilars -- Improving patient care outcomes through navigation -- Patient and family support during and after cancer therapy -- Public and professional cancer resources.
Includes bibliographical references and index.
Keywords: Antineoplastic Agents -- therapeutic use; Neoplasms -- drug therapy